Improvement in Asthma Symptoms and Pulmonary Function in Children After SARS-CoV-2 Outbreak - Taytard, Jessica; Coquelin, Florence; Beydon, Nicole (Frontiers in Pediatrics, 2021)
Introduction: Little is known on the effect of SARS-CoV-2 circulation on asthma daily symptoms in children. We compared asthma exacerbations, asthma symptom control and lung function before and after SARS-CoV-2 outbreak in children. Methods: Retrospective study of children with persistent asthma referred for lung function testing. The second quarter of 2020 being a period with nearly no activity, we compared the activity between the first, third and fourth quarters of 2019 and 2020 (Q1-2019 versus Q1-2020, Q3-2019 versus Q3-2020, and Q4-2019 versus Q4-2020). Results: We retrieved 1871 files in 2019 and 1548 in 2020. The whole population (2165 (63.3%) boys) had a median [IQR] age of 9.7 [6.8;13.1] years. There was no difference in age, sex and ethnicity between 2019 and 2020 populations. Asthma was better controlled during Q4-2020 compared to Q4-2019 (P = 0.042), and there was a lower proportion of children with at least one exacerbation in the previous 3 months after the reopening, compared to the same period in 2019 (P < 0.0001). Baseline FEV1 (Z-score) recorded after the reopening was significantly higher (with less reversibility) compared to the same period before the epidemic (P < 0.0001). Baseline FEV1/FVC (Z-score) was significantly higher during Q3-2020 compared to Q3-2019 (P = 0.026), with fewer children having a significant reversibility (P = 0.035). Discussion: We demonstrated a trend towards increased exacerbations just before the recognition of the epidemic, and fewer exacerbations, better asthma symptom control and improvement in the lung function of asthmatic children after the reopening.